Voter Education to Increase Community Participation in the 2024 General Elections (Case Study of KPU Malang Regency) - Bayu Karunia Putra; Azizatul Farhaini; Dinatul Aini; Siti Nurjannah; Noviana Noviana; Raudatul Ismi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aims to determine the implementation of voter education programs to increase community participation in the 2024 general election in Malang Regency. Topic is important and interesting, because increasing public participation has a great influence in conducting elections, coupled with the existence of socialization and political education which is one of the foundations for strong to build the level of voter participation in using their voting rights as well as possible, especially during the general election in 2024. This research method is a method that uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. Sources of data in the study were obtained through interviews, observation, and online media. Data collection and data analysis techniques in this study were using interview, observation, and online media techniques carried out by researchers to collect, explore, and collect valid, complete, and relevant information related to the topic of the problem that became the object of research. The author finds that, related to political education, it is very useful as a strategy to increase a high participatory attitude in using their voting rights as well as possible, because this strategy is a good step to encourage them to become agents of change, so that awareness of rights politics, democracy, and community participation can be improved further.